MO166: The Longitudinal Evolution of Covid-19 Outcomes Among Hemodialysis Patients: A Nationwide Multicentre Controlled Study. (3rd May 2022) - Ozturk, Savas; Turgutalp, Kenan; Arici, Mustafa; Gorgulu, Numan; Zeki Tonbul, Halil; Eren, Necmi; Gencer, Vedat; Ayli, Deniz; Pembegul, Irem; Esra Dolarslan, Murside; Ural, Zeynep; Colak, Hulya; et al.
Abstract: BACKGROUND AND AIMS: Haemodialysis (HD) patients are at increased risk for adverse short-term consequences of COVID-19. In this study, we investigated the characteristics of chronic HD patients in the post-COVID-19 period and compared them with the control group. METHOD: We conducted a national multicentre observational study involving adult chronic HD patients recovering from COVID-19. The control HD group was selected from patients with similar characteristics who did not have COVID-19 in the same center. SARS-CoV-2 RT-PCR negative patients and patients in the active period of COVID-19 were not included. RESULTS: A total of 1223 patients (635 COVID-19 groups, 588 control groups) were included in the study from the data collected from 47 centres between 21 April 2021 and 11 June 2021. The patients' baseline demographics, comorbidities, medications, HD characteristics and basic laboratory tests were quite similar between the groups (Table 1). 28th-day mortality and between 28th day and 90th day mortality were higher in the COVID-19 group than in the control group [19 (3.0%) patients and 0 (0%) patients; 15 (2.4%) patients and 4 (0.7%) patients, respectively]. Presence of respiratory symptoms, rehospitalization, need for home oxygen therapy, lower respiratory tract infection and A-V fistula thrombosis were significantly higher in the COVID-19 group in the first 28 days of illness and between 28 and 90 days. Mortality was significantly associated with preexisting COVID-19, age, current smoking, use of tunneled HD catheter, persistence of respiratory symptoms, rehospitalization, need for home oxygen support, presence of lower respiratory tract infection within 28 days and persistence of respiratory symptoms. CONCLUSION: In the post-COVID-19 period, mortality, rehospitalization, respiratory problems and vascular access problems are higher in maintenance HD patients who have had COVID-19 compared to control HD patients.